Effects of extended transport on cryopreserved allogeneic hematopoietic progenitor cell (HPC) product quality and optimal methods to assess HPC stability. Issue 4 (28th March 2023) - Reddy, Opal L.; Sall, Mame Thioye; Dinh, Anh; Cai, Yihua; Ongkeko, Martin; Arya, Nina; Wilder, Jennifer; Tran, Minh; Jin, Ping; Stroncek, David F.; Panch, Sandhya R.
Abstract: Background: Since the beginning of the COVID‐19 pandemic, cryopreservation of hematopoietic progenitor cell (HPC) products has been increasingly used to ensure allogeneic donor graft availability prior to recipient conditioning for transplantation. However, in addition to variables such as graft transport duration and storage conditions, the cryopreservation process itself may adversely affect graft quality. Furthermore, the optimal methods to assess graft quality have not yet been determined. Study Design and Methods: A retrospective review was performed on all cryopreserved HPCs processed and thawed at our facility from 2007 to 2020, including both those collected onsite and by the National Marrow Donor Program (NMDP). HPC viability studies were also performed on fresh products, retention vials, and corresponding final thawed products by staining for 7‐AAD (flow cytometry), AO/PI (Cellometer), and trypan blue (manual microscopy). Comparisons were made using the Mann–Whitney test. Results: For HPC products collected by apheresis (HPC(A)), pre‐cryopreservation and post‐thaw viabilities, as well as total nucleated cell recoveries were lower for products collected by the NMDP compared to those collected onsite. However, there were no differences seen in CD34+ cell recoveries. Greater variation in viability testing was observed using image‐based assays compared to flow‐based assays, and on cryo‐thawed versus fresh samples. No significant differences were observed between viability measurements obtained on retention vials versus corresponding final thawed product bags. Discussion: Our studies suggest extended transport may contribute to lower post‐thaw viabilities, but without affecting CD34+ cell recoveries. To assess HPC viability prior to thaw, testing of retention vials offers predictive utility, particularly when automated analyzers are used.